2009
DOI: 10.5558/tfc85227-2
|View full text |Cite
|
Sign up to set email alerts
|

Standing deadwood for keystone bird species in the eastern boreal forest: Managing for snag dynamics

Abstract: Extensive even-aged management of the boreal forest and its consequences on the loss of late-seral stages (>100 years) is raising concerns about the future of organisms associated with standing deadwood. The considerable reduction of deadwood not only at the stand but at the landscape level is considered to be one of the principal causes of biodiversity loss in managed forest ecosystems worldwide. Ecosystem-oriented management approaches propose a fundamental change in forestry practices whereby live and dead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 47 publications
2
63
0
Order By: Relevance
“…In our analysis, dead wood of the first class decay represented by large branches on the ground or standing dead trees and stumps belonging to the third class decay affect positively the richness and abundance of xylophagous beetles that attack fresh dead wood, while standing dead trees belonging to the fourth class decay and dead trees on the ground of second class decay affect hole nesting-birds. In accordance with our results, several studies have shown that unremoved dead wood on the ground (e.g., Johansson et al 2007) or artificially created dead wood microhabitats (e.g., Lindhe and Lindelöw 2004), are used for beetle development and consequently important for hole-nesting bird foraging activity, because the number of trees required for foraging is considerably larger than the number of nest trees (Drapeau et al 2009). …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In our analysis, dead wood of the first class decay represented by large branches on the ground or standing dead trees and stumps belonging to the third class decay affect positively the richness and abundance of xylophagous beetles that attack fresh dead wood, while standing dead trees belonging to the fourth class decay and dead trees on the ground of second class decay affect hole nesting-birds. In accordance with our results, several studies have shown that unremoved dead wood on the ground (e.g., Johansson et al 2007) or artificially created dead wood microhabitats (e.g., Lindhe and Lindelöw 2004), are used for beetle development and consequently important for hole-nesting bird foraging activity, because the number of trees required for foraging is considerably larger than the number of nest trees (Drapeau et al 2009). …”
Section: Discussionsupporting
confidence: 77%
“…decay stage, diameter, typology) rather than quantity for the maintenance of saproxylic diversity. In particular, deadwood diversity was considered as a better indicator of animal diversity than volume per se (Drapeau et al 2009, Similä et al 2003, Jacobs et al 2007, Brin et al 2009, Lassauce et al 2011, Gossner et al 2013, Lachat et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Coarse woody debris (CWD), snags and downed logs, is a key attribute of forest ecosystems, sustaining a myriad of species [47,48] and structural diversity [49], as well as contributing to seedling establishment [30]. One underlying objective of partial harvesting in the context of ecosystem management is to increase the recovery time of CWD dynamics following harvesting [50].…”
Section: Recruitment and Volume Of Deadwood Following Partial And Clementioning
confidence: 99%
“…The duration of time from recruitment to falling down, which is often referred to as snag longevity, not only determines snag abundance but also is closely related to the quality of the habitats provided to species associated with snags. The assemblage of species associated with snags varies by several factors, including tree species, diameter, sun exposure, burn treatment, and decay condition of snags (Drapeau et al 2009;Gibb et al 2006;Jonsell et al 1998;Saint-Germain et al 2007;Ulyshen and Hanula 2009). Snag longevity influences the succession of the species assemblages through progression of the decay stage, and the process is usually categorized into five or more stages (Stokland et al 2012).…”
Section: Introductionmentioning
confidence: 99%